IMPLEMENTASI PROJECT-BASED LEARNING PENGUATAN PROFIL PELAJAR PANCASILA DI SMAN 1 KOTA SUKABUMI - Tantan Hadian; Rachmat Mulyana; Nana Mulyana; Ida Tejawiani (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This article describes and analyzes the implementation of the Pancasila Student ProfileStrengthening Project (P5) at SMA Negeri 1 Sukabumi. The research is qualitative-descriptive design. The research was conducted by analyzing the planning, organization, implementation, and evaluation of projects implemented at school. The research begins with a documentation study, distributing questionnaires to 32 teachers as respondents, interviews, and observations. The results are planning, which includes team formation, making technical guidebooks, and determining project themes. Meanwhile, project organization consists of the formation of a project group guidance team, determining the object of research, and determining student groups. The implementation of the project starts with determining the formulation of the research object, formulating the problems, making instruments, implementing observations, making reports, and creating blogs to upload project reports. Whilst project supervision and evaluation are conducted in the supervision internally and externally. The theme of the first project is local wisdom, the second project is engineering technology. The project is implemented through a block system within 3-4 weeks. The end of the project is carried out through the harvest of works, namely publication in the form of presentations of students’ work, which is attended by students, teachers, and parents either in offline or online meetings. The finding of the research problem comes from the lack of coordination of school management internally and externally with a percentage of 46% of teacher respondents are not involved in the planning of the project and the lack of school supervisors and school committees’ roles. Another finding comes from the lack of student activity with a percentage of only 59% who actively participated in making the project activity. The assessment and project objectives do not reflect the achievement of the Pancasila student profile.